2013
DOI: 10.1089/neu.2012.2647
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Alpha/Beta-Hydrolase Domain 6 Attenuates Neurodegeneration, Alleviates Blood Brain Barrier Breakdown, and Improves Functional Recovery in a Mouse Model of Traumatic Brain Injury

Abstract: 2-arachidonylglycerol (2-AG) is the most abundant endocannabinoid in the central nervous system and is elevated after brain injury. Because of its rapid hydrolysis, however, the compensatory and neuroprotective effect of 2-AG is short-lived. Although inhibition of monoacylglycerol lipase, a principal enzyme for 2-AG degradation, causes a robust increase of brain levels of 2-AG, it also leads to cannabinoid receptor desensitization and behavioral tolerance. Alpha/beta hydrolase domain 6 (ABHD6) is a novel 2-AG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(126 citation statements)
references
References 82 publications
7
119
0
Order By: Relevance
“…Mice prefer to enter a maze arm that was not previously explored, so the test requires the animals to recall which arm was most recently entered. 35 Overall, performance of sham-treated mice was significantly superior to that of animals with severe CCI, as described previously, 34 but there was a statistical main effect of sex, with females having poorer performance (Fig. 5A).…”
Section: Traumatic Brain Injury Equally Impairs Motor Coordination Onsupporting
confidence: 80%
See 1 more Smart Citation
“…Mice prefer to enter a maze arm that was not previously explored, so the test requires the animals to recall which arm was most recently entered. 35 Overall, performance of sham-treated mice was significantly superior to that of animals with severe CCI, as described previously, 34 but there was a statistical main effect of sex, with females having poorer performance (Fig. 5A).…”
Section: Traumatic Brain Injury Equally Impairs Motor Coordination Onsupporting
confidence: 80%
“…34,35 The apparatus consisted of three arms at a 120-degree angle to one another with a triangular central zone. Each arm was 36 cm in length, enclosed by walls 16 cm high, and a small visual cue was placed at the distal wall of each arm.…”
Section: Y-maze Spontaneous Alternationmentioning
confidence: 99%
“…By contrast, in the neonatal rat brain, the exposure to concussive head trauma induced a moderate increase in the levels of anandamide and other N-acylethanolamines, but not of 2-AG and other 2-monoacylglycerols [43,44]. Further studies demonstrated that these elevations are endogenous responses addressed to limit brain damage, as the inhibition of 2-AG and anandamide hydrolysis reduced brain damage and improved functional deficits in parallel to a reduction of proinflammatory responses in the mouse brain after TBI [45,46]. Similar elevations of anandamide, 2-AG, and Nacylethanolamines have been detected in experimental cerebral ischemia [47][48][49][50].…”
Section: Cannabinoids and Acute Brain Damage: Stroke And Brain Traumamentioning
confidence: 96%
“…Indeed, ABHD6 has recently been shown to regulate 2-AG degradation and signaling in murine primary neurons and cortical slices (Marrs et al, 2010) and control 2-AG accumulation in the Neuro2A cell line, which lacks MAGL (Hsu et al, 2012). Additionally, ABHD6 inhibition in vivo produced CB1-and CB2-mediated anti-inflammatory and neuroprotective effects in a mouse model of traumatic brain injury (Tchantchou and Zhang, 2012). Human genetics has implicated ABHD12 as a critical regulator of neurologic function; loss-of-function mutations in ABHD12 cause the human neurodegenerative disease PHARC (polyneuropathy, hearing loss, ataxia, retinosis pigmentosa, and cataract) (Fiskerstrand et al, 2010), although whether ABHD12-disruption leads to neuronal death by dysregulation of 2-AG or an alternate mechanism remains to be determined.…”
Section: B 2-ag Hydrolysis By Monoacylglycerol Lipasementioning
confidence: 99%